Peran Pustakawan dalam Meningkatkan Kinerja Perpustakaan (Studi Kasus di Perpustakaan MAN I Makassar) - Chusnul Chatimah Asmad; Taufiq Mathar (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2015)
A school library plays important roles to support education learning-process in school. However, many school libraries in fact lack of aware its roles. The most reason why it happened due to lack of understanding how to organize a school library. The current study investigates one of Islamic High School libraries in Makassar, which is Madrasah Aliyah Negeri 1 Makassar. Based on the pre-observation, it is shown that there was a significant role done by its school librarians. The data is collected throughout interviews with the chief of school, students, and some teachers as well. The result findings depicted that school librarians have optimally played their roles as school librarians. However, it remains some barriers such as less aware from the school authoritative, collections, budget, and facilities.